2010
DOI: 10.1007/s00435-010-0116-6
|View full text |Cite
|
Sign up to set email alerts
|

Ovaries of Tubificinae (Clitellata, Naididae) resemble ovary cords found in Hirudinea (Clitellata)

Abstract: The ultrastructure of the ovaries and oogenesis was studied in three species of three genera of Tubificinae. The paired ovaries are small, conically shaped structures, connected to the intersegmental septum between segments X and XI by their narrow end. The ovaries are composed of syncytial cysts of germ cells interconnected by stable cytoplasmic bridges (ring canals) and surrounded by follicular cells. The architecture of the germ-line cysts is exactly the same as in all clitellate annelids studied to date, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 42 publications
8
39
2
Order By: Relevance
“…In this section, we concentrate on the details of the ovary cord composition and oogenesis in arhynchobdellid leeches (Table 1). A comparison between all of the groups of clitellate annelids studied to date was presented recently (Urbisz et al, 2010). As is summarized in Table 1, the general organization of ovaries and oogenesis in the arhynchobdellid leeches studied to date is similar; however, there are several differences.…”
Section: Comparison Of Ovary Organization and Oogenesis In Arhynchobdmentioning
confidence: 95%
See 4 more Smart Citations
“…In this section, we concentrate on the details of the ovary cord composition and oogenesis in arhynchobdellid leeches (Table 1). A comparison between all of the groups of clitellate annelids studied to date was presented recently (Urbisz et al, 2010). As is summarized in Table 1, the general organization of ovaries and oogenesis in the arhynchobdellid leeches studied to date is similar; however, there are several differences.…”
Section: Comparison Of Ovary Organization and Oogenesis In Arhynchobdmentioning
confidence: 95%
“…These cysts have a characteristic spatial arrangement; each germ cell in a given cyst has only one RC connecting it to a common anuclear cytoplasmic mass -the cytophore. Numerous studies have shown that the formation of germline cysts with a central cytophore is a conserved phase of gametogenesis in Clitellata (Fernández et al, 1992;Ferraguti, 1999;Jamieson, 2006;Krüger et al, 2008;Spałek-Wołczyńska et al, 2008;Swiątek, 2005bSwiątek, , 2008Świątek et al, 2009Ben Ahmed et al, 2010) and should be regarded as a primary condition (Urbisz et al, 2010;Świątek et al, 2012). Similar germline cysts with a central cytoplasmic mass have been found during gametogenesis in some Polychaeta, Plathyhelmintes and Nematoda (Sawada, 1975;Hirsh et al, 1976;Foor, 1983;Gibert et al, 1984;Sopott-Ehlers, 1989).…”
Section: Germline Cystsmentioning
confidence: 97%
See 3 more Smart Citations